2021
DOI: 10.1192/bji.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health problems among Syrians during war and the COVID-19 pandemic: national survey

Abstract: This study aims to assess the prevalence of depression and anxiety during the COVID-19 outbreak embedded within the war in Syria. A web-based cross-sectional survey design was employed. The 9-item Patient Health Questionnaire and the 7-item Generalized Anxiety Disorder scale revealed a high prevalence of depressive (n = 3326; 83.4%) and anxiety symptoms (n = 2777; 69.6%) among the 3989 participants. Multivariable logistic regression analysis was performed to identify factors associated with depression and anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…Elhadi et al, 2020, found that in response to the civil war in Libya, female medical students had higher scores of GAD-7 than their male colleagues [ 53 ]. Likewise, during the Syrian civil war, female adults were 1.5 times more likely to suffer from anxiety disorders than males assessed by GAD-7 [ 54 ]. Additionally, female Libyan adults had a significantly higher GAD-7 score than their male counterparts following the COVID-19 lockdown [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elhadi et al, 2020, found that in response to the civil war in Libya, female medical students had higher scores of GAD-7 than their male colleagues [ 53 ]. Likewise, during the Syrian civil war, female adults were 1.5 times more likely to suffer from anxiety disorders than males assessed by GAD-7 [ 54 ]. Additionally, female Libyan adults had a significantly higher GAD-7 score than their male counterparts following the COVID-19 lockdown [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This problem was worrying as it did lead to a build-up of vulnerable individuals. The COVID-19 measure has contributed to the worsening of some mental illnesses or even the emergence of new ones in Syrian refugees and parents [ 5 7 ]. Some of these could be related to financial difficulties, as most workers in the camps stopped working.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we implemented an intervention study to support parents and caregivers in Zaatari camp during the COVID-19 pandemic using a leaflet on caregiving under COVID-19 developed by the United Nations Office on Drugs and Crime (UNODC) [ 13 ]. This leaflet was delivered using a smartphone application (app) called the Children Immunization App (CIMA) [ 5 ]. The CIMA is a vaccination reminder app that has already been implemented in Zaatari camp since 2019.…”
Section: Introductionmentioning
confidence: 99%
“…This percentage corresponds to a previous study conducted in Syria during the war and the COVID-19 pandemic, which reported the prevalence of depressive symptoms to be 83.4%. [15] Given that a strong correlation between the presence of depressive symptoms and a diagnosis of FM has been demonstrated in previous literature, this high percentage of depressive symptoms is of concern as there is growing evidence of a possible link between the two. [16,17] One study showed that 83.3% of FM subjects had clinically signi cant depressive symptoms, while another demonstrated prevalence rates of up to 40%.…”
Section: Relationship Between Bdi and Patients With Bromyalgiamentioning
confidence: 99%